Firms' Evaluation of Location Quality: Evidence from East Germany - Alexander Eickelpasch; Georg Hirte; Andreas Stephan (Jahrbücher für Nationalökonomik und Statistik, 2016)
Our study provides evidence for firms' evaluation of location quality. We use a 2004 survey of 6,000 East German firms that contained questions on the importance and assessment of 15 different location factors ranging from closeness to customers and suppliers, transport infrastructure, and proximity to research institutions and universities, as well as questions about the local financial institutions and region's “image”. The results show (1) a great deal of heterogeneity in terms of which firm- or regional-level characteristics are important in the evaluation of a specific location factor, (2) that the model's explanatory power is, overall, low and thus neither location characteristics nor internal factors are fully reflected in the perceptions of location quality, (3) that a firm's business situation and whether a location factor is considered important have explanatory power for perception. One policy-relevant conclusion that we derive from these findings is that location policy should consider firms' perception of a specific location in addition to improving the actual attributes of that location
Additional information: This article is available under http://dx.doi.org/10.1515/jbnst-2015-1014
Keywords: 330; location factors; multi-equation system; perception bias; survey data